Soft and hard TQM practices: future research agenda for industry 4.0 - Ali, K. (Routledge, 2021)
The primary objective of this study is to examine the present literature of Total Quality Management (TQM) and its connection with industry 4.0. The author tried to understand what subject and problems might be deemed more relevant, referring to the so-called Quality 4.0, which is absent from the literature to open avenues for further research. To achieve the primary objective, the author reviewed the literature on TQM from the objective (soft) and subjective (hard) perspectives, followed by identifying the critical success factors and future research avenues for researchers. A total of 87 empirical studies from 1987â2019 were studied. The descriptive and thematic analysis identified the soft and hard total quality management practices. A quality tool, âPareto Analysisâ, was applied to soft and hard TQM practices. The comprehensive review identified 23 soft and 15 hard TQM practices in the manufacturing and services sectors. The findings revealed four soft dimensions for the effective implementation of Quality 4.0 in business: Top management commitment, customer focus, training and learning, and quality of big data and analysis. Furthermore, three hard dimensions revealed the effective implementation of Quality 4.0: process management, continuous improvement, and product/service design. Â© 2021 Informa UK Limited, trading as Taylor & Francis Group.